2015
DOI: 10.1002/2015gc005831
|View full text |Cite
|
Sign up to set email alerts
|

Particle dynamics in the rising plume at Piccard Hydrothermal Field, Mid‐Cayman Rise

Abstract: Processes active in rising hydrothermal plumes, such as precipitation, particle aggregation, and biological growth, affect particle size distributions and can exert important influences on the biogeochemical impact of submarine venting of iron to the oceans and their sediments. However, observations to date of particle size distribution within these systems are both limited and conflicting. In a novel buoyant hydrothermal plume study at the recently discovered high-temperature (3988C) Piccard Hydrothermal Fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
(125 reference statements)
0
9
0
Order By: Relevance
“…Earlier studies indicated that Fe and Mn oxyhydroxides are important for the scavenging of dissolved seawater constituents in the hydrothermal plumes [ Berner , ; Trefry and Metz , ]. These particles also disperse with the plume [ Dymond , ; Feely et al ., , ; Wang et al ., ; Estapa et al ., ], and are probably transported hundreds of kilometers, as observed in the deep Pacific Ocean [ Siegel et al ., ]. Toner et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Earlier studies indicated that Fe and Mn oxyhydroxides are important for the scavenging of dissolved seawater constituents in the hydrothermal plumes [ Berner , ; Trefry and Metz , ]. These particles also disperse with the plume [ Dymond , ; Feely et al ., , ; Wang et al ., ; Estapa et al ., ], and are probably transported hundreds of kilometers, as observed in the deep Pacific Ocean [ Siegel et al ., ]. Toner et al .…”
Section: Discussionmentioning
confidence: 98%
“…To date, three active zones, extending laterally 1000 m, have been found [Tao et al, 2012]. Since limited hydrothermal vents have been confirmed on ultraslow-spreading ridges [German et al, 1998;Tao et al, 2012], their influence on either heat balance or chemical budgets in the global oceans has received only limited examination [Bach et al, 2002;Estapa et al, 2015]. A few studies indicate that a hydrothermal effluent plume on the ultraslowspreading ridge (i.e., Gakkel Ridge in the Arctic Ocean) also adds large amounts of chemicals to oceans in a manner similar to that of fast-spreading ridges [German et al, 1998;Edmonds et al, 2003;Statham et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…The residence times of particulate 210 Po at the slope stations (i.e., 105A and 91) ranged from 0.11 to 0.16 year within the mesopelagic layer (averaging 0.13 ± 0.04 year), comparable to the residence times of TPM in a hydrothermal plume over the Southwest Indian Ridge [ Yang et al ., ]. Such a time scale allows particulate matter to move over a very long range as proved in general deep water [ Siegel et al ., ] and in the mesopelagic or bathypelagic hydrothermal plumes [ Wang et al ., ; Estapa et al ., ]. Thus, the residence times of particulate 210 Po provide supports for the transport of resuspended shelf sediment into the SCS basin.…”
Section: Discussionmentioning
confidence: 99%
“…However, as emphasized by Rudnicki and German (2002), plume heights can vary with time. Estapa et al (2015) place the maximum plume height at approximately 4,100 m depth, 150 m below the value of German, Bowen, et al (2010), although it is possible that the plume rises higher than this given the apparent uncertainties. To compensate for changes in the maximum height, we use 3,950 ± 150 m as the top of the Piccard plume.…”
Section: Heat and Mass Fluxes At Piccardmentioning
confidence: 94%